3D Bioprinting of Developmentally Inspired Templates for Whole Bone Organ Engineering. Issue 18 (9th June 2016) - Daly, Andrew C.; Cunniffe, Gráinne M.; Sathy, Binulal N.; Jeon, Oju; Alsberg, Eben; Kelly, Daniel J.
Abstract : The ability to print defined patterns of cells and extracellular‐matrix components in three dimensions has enabled the engineering of simple biological tissues; however, bioprinting functional solid organs is beyond the capabilities of current biofabrication technologies. An alternative approach would be to bioprint the developmental precursor to an adult organ, using this engineered rudiment as a template for subsequent organogenesis in vivo. This study demonstrates that developmentally inspired hypertrophic cartilage templates can be engineered in vitro using stem cells within a supporting gamma‐irradiated alginate bioink incorporating Arg‐Gly‐Asp adhesion peptides. Furthermore, these soft tissue templates can be reinforced with a network of printed polycaprolactone fibers, resulting in a ≈350 fold increase in construct compressive modulus providing the necessary stiffness to implant such immature cartilaginous rudiments into load bearing locations. As a proof‐of‐principal, multiple‐tool biofabrication is used to engineer a mechanically reinforced cartilaginous template mimicking the geometry of a vertebral body, which in vivo supported the development of a vascularized bone organ containing trabecular‐like endochondral bone with a supporting marrow structure. Such developmental engineering approaches could be applied to the biofabrication of other solid organs by bioprinting precursors that have the capacity to mature into their adult counterparts over time in vivo. Abstract : A novel biofabrication strategy is described where 3D bioprinting is used to engineer the developmental precursor to an adult organ. These bioprinted cartilage templates have the capacity to mature into vascularized bone organs in vivo. It was possible to reinforce these immature cartilage precursors with polycaprolactone microfibres, providing a level of mechanical functionality compatible with implanting such immature organ rudiments into load bearing locations in vivo.